2018
DOI: 10.1371/journal.pone.0203410
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorder tied to development of chronic kidney disease: A nationwide database analysis

Abstract: IntroductionAlcohol use disorder (AUD) is a spectrum of high risk behaviors including alcohol abuse and dependence. Chronic kidney disease (CKD) is progressive loss of renal function for more or equal to 3 months or presence of any irreversible kidney damage. Common risk factors of CKD have been identified, but the impact of alcohol consumption on kidney function is controversial. The study aims to investigate the relationship between alcohol use disorder and CKD on a national scale.MethodsThis retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
3
30
1
Order By: Relevance
“…Chronic kidney disease (CKD) has shown to be associated with atherosclerosis [39,40]. Although few studies have suggested a harmful association between alcohol consumption and CKD, our study found no such association [41,42].…”
Section: Potential Mechanismscontrasting
confidence: 79%
“…Chronic kidney disease (CKD) has shown to be associated with atherosclerosis [39,40]. Although few studies have suggested a harmful association between alcohol consumption and CKD, our study found no such association [41,42].…”
Section: Potential Mechanismscontrasting
confidence: 79%
“…In their study, excessive alcohol consumption is associated with a higher odds ratio of CKD than in the abstainer. Other studies also found a higher association between heavy drinking and albuminuria or CKD, particular among young and middle-aged men [4,67,73,74]. However, Kimura et al found a U-shaped and J-shaped association between alcohol consumption and the incidence of proteinuria in men and women, respectively.…”
Section: Association Between Alcohol Consumption and Chronic Kidney Dmentioning
confidence: 96%
“…Age, primary diseases, initial eGFR, and individual differences can also affect the prognosis of patients with CKD and interfere with the effects of alcohol on the kidneys [7,10,67,94]. Since aging, metabolic diseases, and hypertension impair kidney function, they can also influence the effect of ethanol on the kidneys.…”
Section: Association Between Alcohol Consumption and Chronic Kidney Dmentioning
confidence: 99%
“…Affected by the global population aging, chronic kidney disease (CKD), the 17th leading cause of death worldwide (1), is becoming a worldwide public health and can lead to a series of adverse health outcomes including premature death, poor quality of life, and cardiovascular disease (2)(3)(4). Moreover, smoking, alcohol use disorder, and obesity are all well-known risk factors for CKD (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%